Foreign investment in the fishing sector after the Free Trade Agreement between Peru and China, 2009-2021 - Maldonado-Cueva, Percy David; Criado-Dávila, Yvette Vanessa; Fernandez-Bedoya, Víctor Hugo (LACCEI, 2024)
Peru relies on abundant marine resources, notably anchovy, for its fishing sector, exporting species like mackerel and giant squid. The Peru-China Free Trade Agreement (FTA) facilitated significant 2021 exports to China, totaling 1.4 million metric tons, while imports were 598.8 thousand MT. Chinese investments primarily target mining, hydrocarbons, and fisheries, particularly through acquiring existing companies. The article investigates the impact of foreign investment in the fishing sector under the Peru-China FTA (2009-2021). Utilizing a non-experimental descriptive methodology with data from INEI and the Ministry of Production, the study concludes that such investments have not substantially benefited Peru, as reflected in the absence of significant economic and technological changes in its workforce